Higher Order Thinking Skills Analysis on Problems in Class XI SMA Physics Books - Sudirman Sudirman; Saparini Saparini; Fathiyyah Yasmin; Muhammad Saukani (Universitas Lambung Mangkurat, 2023)
Currently, schools are expected to be able to train students to get used to solving higher-order thinking questions, one of which is through the textbooks the teacher chooses to teach. This study aimed to analyze the types of Higher Order Thinking Skills (HOTS) questions in Physics textbooks for class XI students. Data was collected using documentation techniques. The documents are physics textbooks from four publishers: Erlangga, Grafindo, Yrama Widya, and Intan Pariwara. Data analysis in the form of the percentage of HOTS questions in each book was calculated quantitatively and then discussed qualitatively related to these results. The results showed that the distribution of HOTS questions in (1) Erlangga textbooks was 8% in chapter 1 and 8% in chapter 2; (2) Grafindo textbooks by 20% in chapter 1 and 20% in chapter 2; (3) Yrama Widya textbooks by 43% in chapter 1 and 50% in chapter 2; (4) Intan Pariwara textbooks by 55% in chapter 1 and 40% in chapter 2. Among the four textbooks, the book published by Intan Pariwara has the highest distribution of HOTS questions. Based on this result, teachers can use this book to carry out learning evaluations to measure students' HOTS abilities.